The Wright Brothers : The First Flyers
The Wright Brothers, or the First Flyers, are the legendary duo who gave people wings to fly. They are responsible for inventing an airplane that could actually be controlled in air. All the airplane journeys that we take for granted today would not have been possible without the Wright Brothers first successful controlled and powered human flight that gave people a new and speedy means of travelling across the world.Join the curious and playful Digby and his big sister Hester as they make their way through the odds and ends at Mr Rummages stall at Knick-Knack Market. Discover the wonderful little objects they pick up and enjoy the stories about the great people they belong to.This book:tells the factual biography of the great aviators, Wilbur and Orville Wright within an exciting storybrings their aeronautical innovations and historical flights into a modern settingencourages involvement and fun through drama and dressing-up